RESPONSE ASSESSMENT AND OUTCOMES IN PEDIATRIC B CELL NON-HODGKIN LYMPHOMA: OUR EXPERIENCE AT SHAUKAT KHANUM MEMORIAL CANCER HOSPITAL AND RESEARCH CENTRE - Rehman, Palwasha; Wali, Rabia Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the relation of response assessment and outcome of B cell non-Hodgkinlymphoma so we can minimize utilization of our resources.Study Design: Retrospective observational study.Place and Duration of Study: Pediatric Oncology Department, Shaukat khanum Memorial Cancer Hospital and Research Centre, from Jan 2013 to Dec 2016.Methodology: Patients from the age of 1 till 18 years presented at Shaukat khanum hospital were included in the study. Patients were staged as per St. Jude staging system and response assessment done as per French-American British (FAB) Lymphome Malins De Burkitt (LMB) protocol.Results: Total 247 patients diagnosed with B cell Non-Hodgkin Lymphoma were included. When the interim scans were compared with the end of treatment assessment, 139 (82.2%) patients (n=169) had achieved complete morphological remission on the re-evaluation scans, 138 patients (86.2%) among them were in remission at end of treatment where as 01 patient had relapse disease. The interim disease re-evaluation scan is predictive of end of treatment response with sensitivity of 86.8%, specificity of 88.9% (p-value